Japońska pomoc rozwojowa na rozdrożu: merkantylizm versus humanitaryzm - Kopiński, Dominik (Japan's Development Assistance at the Crossroad: Mercantilism versus Humanitarism, 2008)
Japan is among the major aid-donor nations in the world. For many years being a leading donor in monetary terms, today with 11 bln dollars of aid given in 2006, Japan remains at the third position after the United States and Great Britain. Japanese ODA characteristics make it divergent from the development aid model promoted by the Western countries. While the rest of the OECD members appears to represent increasingly more humanitarian stance and gives priority to poverty alleviation, Japanese philosophy of overseas assistance is inherently mercantilist in nature and provided according to kokueki, which puts the country's prosperity in the centre. Japanese aid is income and regionally biased, with the Asian and middle income countries being the major aid recipients and reflects Japan's strategic national interests, both economic and political. It fails the test of commitment to development. The biggest chunk of the Japanese ODA is directed towards financing hard infrastructure and takes a form of loans rather than grants. Japanese aid has found itself at the crossroad, torn between mercantilist and humanitarian visions. Although the Japanese government, pressured by the international community and its own public opinion, has began reforming ODA, the author suggests that the changes are rather cosmetic and the main pillars of Japanese aid system, at least for the time being, will remain intact. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 125-136